La apuesta asimétrica de Europa en el marco de la crisis - Giuseppe Martinico (Revista Vasca de Administración Pública)
In this brief essay I shall reflect upon one of the options recalled by the recent White Paper of the European Commission and then supported by France, Germany, Italy and Spain in an informal meeting: namely asymmetry. This essay is structured as follows: in a first moment I shall recall how EU Treaties discipline the several asymmetric options present in EU law. In a second moment I shall explore the role acquired by asymmetry with the current European economic crisis. Eventually, I shall present some conclusions on the White Paper with regard to differentiated integration.